Alveolar Repair Using Cancellous Bone and Beta Tricalcium Phosphate Seeded With Adipose-Derived Stem Cell - Putri, Indri Lakhsmi; Fatchiyah; Pramono, Coen; Bachtiar, Indra; Latief, Fourier Dzar Eljabbar; Utomo, Budi; Rachman, Arif; Soesilawati, Pratiwi; Hakim, Lukman; Rantam, Fedik Abdul; Perdanakusuma, David Sontani (The Cleft palate-craniofacial journal, 2024)
Adipose-derived stem cells (ADSCs) have been subject of several studies due to their abundance, ease of preparation, and application in bone regeneration. We aim to compare effectiveness of alveolar reconstruction utilizing human cancellous freeze-dried graft (HCG) and beta tricalcium phosphate (BTP), both seeded with human ADSC (hADSC) and autologous bone graft (ABG). A 5 × 5 mm alveolar defect in 36 male Wistar rats were treated using: ABG (C), HCG-hADSC (H1), and BTP-hADSC (H2). At 1 and 8 weeks after surgery, runt-related transcription factor 2 (RUNX2), alkaline phosphatase (ALP), osterix (OSX), and bone morphogenetic protein 2 (BMP2; g/mL) were quantified using immunohistochemistry, while bone tissue volume (BV, mm ), bone tissue volume fraction (BF, percentage), and trabecular thickness of bone (TT, mm) were assessed using micro-computed tomography (CT). One week after surgery, H2 was higher in RUNX2, OSX, ALP, and BMP2 than C ( < .05). Only RUNX2 and OSX were found to be higher in H1 than C, while ALP and BMP2 were higher in H2 than H1. Micro-CT revealed that H2 had a higher TT than C and C had a higher TT than H1 ( < .05). Eight weeks after surgery, both H2 and H1 was higher in RUNX2, OSX, ALP, and BMP2 than C ( < .05). RUNX2 and BMP2 were found to be higher in H1 than H2. Micro-CT revealed that H2 had higher BV and TT than C and H1 ( < .05). Exogenous hADSC strengthened the effectiveness of HCG and BTP to accelerate osteogenesis, osteoconduction, and osteoinduction. The latter was the most successful in bone formation, followed by HCG and ABG.